MODEL BASED AND BANDLIMITED SEISMIC INVERSION FOR ACCOUSTIC IMPEDANCE ESTIMATION - Mohamad (NIM 20204026), Febriwan
ABSTRACT: Seismic trace can be generated as a product of convolution between source wavelet function and earth reflectivity. Convolution can reduce seismic trace frequency spectrum, which effect on lack of resolution for low and high frequency. Model based and band-limited inversion method applied to process seismic traces and gaining acoustic impedance (AI) with the support from well data by providing low frequency spectrum. Synthetic data containing noise gives error less than 5percent for every type of noise. For example, applying noise period to synthetic data resulting an error of 0.1percent. For random noise addition, resulting error is 0.2percent and for wavelet noise addition, error obtained were 0.32percent.